2022
DOI: 10.5194/acp-22-4581-2022
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of three types of solar geoengineering on the Atlantic Meridional Overturning Circulation

Abstract: Abstract. Climate models simulate lower rates of North Atlantic heat transport under greenhouse gas climates than at present due to a reduction in the strength of the Atlantic Meridional Overturning Circulation (AMOC). Solar geoengineering whereby surface temperatures are cooled by reduction of incoming shortwave radiation may be expected to ameliorate this effect. We investigate this using six Earth system models running scenarios from GeoMIP (Geoengineering Model Intercomparison Project) in the cases of (i) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
6
22
1
Order By: Relevance
“…It is in the context of this uncertainty that the National Academies of Sciences, Engineering, and Medicine (NASEM) recently called for further research to understand various SCI approaches (NASEM, 2021), as SAI has been shown, in principle, to be a method of global climate intervention capable of achieving various temperature-based targets (Tilmes et al, 2018;MacMartin et al, 2019;Simpson et al, 2019). However, there remain large uncertainties in associated climate responses and impacts (Fasullo et al, 2018;, and adverse effects have been identified involving the water cycle and circulations in the troposphere, stratosphere, and ocean (Tilmes et al, 2018;Kawatani et al, 2011;Watanabe and Kawatani, 2012;Fasullo et al, 2018;Xu et al, 2020;Xie et al, 2022;Sun et al, 2020;Abiodun et al, 2021;Banerjee et al, 2021;Krishnamohan and Bala, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is in the context of this uncertainty that the National Academies of Sciences, Engineering, and Medicine (NASEM) recently called for further research to understand various SCI approaches (NASEM, 2021), as SAI has been shown, in principle, to be a method of global climate intervention capable of achieving various temperature-based targets (Tilmes et al, 2018;MacMartin et al, 2019;Simpson et al, 2019). However, there remain large uncertainties in associated climate responses and impacts (Fasullo et al, 2018;, and adverse effects have been identified involving the water cycle and circulations in the troposphere, stratosphere, and ocean (Tilmes et al, 2018;Kawatani et al, 2011;Watanabe and Kawatani, 2012;Fasullo et al, 2018;Xu et al, 2020;Xie et al, 2022;Sun et al, 2020;Abiodun et al, 2021;Banerjee et al, 2021;Krishnamohan and Bala, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the circulation within the ocean, along with global temperature reductions caused by SAI, could have effects on the ocean temperature distribution (Cao et al, 2016). For large-scale ocean circulation, multiple studies have found that SAI can lead to an acceleration in the Atlantic meridional overturning circulation compared to a scenario without geoengineering (Muthers et al, 2016;Fasullo et al, 2018;Xie et al, 2022).…”
Section: Ocean Circulation and Biogeochemistrymentioning
confidence: 99%
“…The North Atlantic is an atypical region under SAI. The declines in heat transported northwards by the AMOC under greenhouse gas forcing are, to great extent, reversed under all kinds of SRM including SAI (Xie et al, 2022). Thus, great differences exist in SST and air/ocean heat flux between SAI and greenhouse gas climates in the North Atlantic (Yue et al, 2021).…”
Section: Implications For Climate Stabilitymentioning
confidence: 99%
“…Stratospheric Aerosol Intervention (SAI), is a type of SRM that has been widely simulated by many global climate models (e.g., Kravitz et al, 2013), which is accompanied by changing in global circulations such as the NAO teleconnection pattern (Moore et al, 2014), and is known in various models to partially offset the decline in the Atlantic Meridional Overturning Circulation (AMOC; Xie et al, 2022). Undorf et al (2018) simulated the North Atlantic SST cooling accompanied by the historical rise of stratospheric sulfate aerosol from North America and Europe dating back to 1850-1975.…”
Section: Introductionmentioning
confidence: 99%